1985
DOI: 10.1073/pnas.82.3.672
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a platelet-activating factor receptor antagonist isolated from haifenteng (Piper futokadsura): specific inhibition of in vitro and in vivo platelet-activating factor-induced effects.

Abstract: Platelet-activating factor (PAF) is a potent lipid mediator of inflammation and asthma. Using a receptor preparation of rabbit platelet membranes, we identified a novel antagonist of PAF in the methylene chloride extract of a Chinese herbal plant, haifenteng (Piper futokadsura). The active antagonist, kadsurenone, was isolated and characterized in several in vitro and in vivo assays. It is a specific and competitive inhibitor of PAF binding to its receptor with a K; of 5.8x 10-8 M vs. a K; of 6.3 x 10-9 M for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
5

Year Published

1986
1986
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(41 citation statements)
references
References 20 publications
(17 reference statements)
1
35
0
5
Order By: Relevance
“…Discussion Shen et al (1985) have reported pA2 values for kadsurenone of 6.28 with Paf-induced rabbit platelet aggregation and 6.32 with Paf-induced human p.m.n.l. aggregation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Discussion Shen et al (1985) have reported pA2 values for kadsurenone of 6.28 with Paf-induced rabbit platelet aggregation and 6.32 with Paf-induced human p.m.n.l. aggregation.…”
Section: Methodsmentioning
confidence: 99%
“…The binding of Paf to platelet receptors and its human p.m.n.l. aggregating and degranulating actions have recently been shown to be antagonized by the plant-derived compound, kadsurenone (Shen et al, 1985). We have shown that Paf also stimulates the oxidative burst in guinea-pig macrophages (Hartung et al, 1983;Parnham & Leyck, 1983) and initiated the present study on the effects of kadsurenone on pig p.m.n.l.…”
mentioning
confidence: 99%
“…Based on the phospholipids striking biological potency, its stereospecificity, and its ability to desensitize target cells, we suggested that cellular receptors were involved in transducing bioactivity (30)(31)(32). Subsequent studies have indeed demonstrated specific binding sites for PAF in or on platelets, PMN, and smooth muscle-containing tissues (33)(34)(35)(36) while other studies have identified compounds that competitively inhibit PAF binding and bioactions (37)(38)(39). In this report, we examine PAF metabolism concurrently with binding, track the subcellular movement of PAF and its metabolites, and characterize the location of PAF receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Although several specific PAF-receptor antagonists, chemically related (Terahsita et al, 1983;Steiner et al, 1985) and unrelated to PAF (Braquet et al, 1985;Komecki et al, 1984;Hwang et al, 1985;Shen et al, 1985), have recently been reported, human pharmacology is very limited (Chung etal., 1987). Here we report that (RS)-2-methoxy-3-(octadecylcarbamoyloxy)-propyl 2-(3-thiazolio) ethylphosphate (CV-3988) (Terashita et al, 1983), when administered intravenously to human volunteers, inhibits PAF induced platelet aggregation ex vivo.…”
Section: Introductionmentioning
confidence: 99%